Indoor residual spraying uptake and its effect on malaria morbidity in Ngoma district, Eastern province of Rwanda, 2018–2021 - Olivier Nsekuye; Samuel S. Malamba; Jared Omolo; Ziad El-Khatib; Jean-Louis N. Mangara; Dunia Munyakanage; Angela Umutoni; Naomi W. Lucchi; Edson Rwagasore; Samuel Rwunganira; Aline Uwimana; Daniel Ntabanganyimana; et al. (Malaria Journal)
Abstract Background Indoor residual spraying (IRS) has been implemented in Rwanda in districts with high malaria transmission, including Ngoma District. The first IRS campaign (IRS-1) was conducted in March 2019, ahead of the peak malaria season, followed by a second campaign (IRS-2) in August 2020, targeting 89,331 structures. This study assessed factors influencing IRS uptake and evaluated the impact of IRS interventions on malaria morbidity in Ngoma District, Eastern Province, Rwanda. Methods A household survey employing multistage cluster sampling design was conducted in May 2021 to randomly select households. A structured questionnaire was administered to the head of household or a designated representative. Logistic regression, adjusted for the complex survey design and weighted for sampling, was used to identify factors associated with IRS uptake. Additionally, secondary data on malaria cases registered in the Rwanda Health Management Information System (RHMIS) from January 2015 to December 2022 were analyzed using interrupted time series analysis to evaluate the effect of IRS on malaria morbidity. Results A total of 636 households participated in the survey. Households headed by self-employed individuals (aOR = 0.07; 95% CI 0.01–0.55) and unemployed individuals (aOR = 0.18; 95% CI 0.03–0.99) were less likely to take up IRS compared to those headed by farmers. Households receiving IRS information through media channels (aOR = 0.01; 95% CI 0.00–0.17) were less likely to participate compared to those informed by community health workers. From the RHMIS data, 919,843 malaria cases were identified from January 2015 to December 2022. Interrupted time series analysis revealed that the baseline number of adjusted malaria cases was approximately 16,920. The first IRS intervention in March 2019 resulted in a significant reduction of 14,380 cases (p < 0.001), while the second intervention in August 2020 led to a reduction of 2495 cases, though this was not statistically significant (p = 0.098). Conclusion This study demonstrates the effectiveness of IRS in reducing malaria incidence in Ngoma District and highlights the role of socioeconomic factors and sources of information in influencing IRS uptake. To maximize the impact of IRS and ensure equitable benefits, targeted strategies, enhanced IRS education, and integrated malaria control approaches, including the use of bed nets, are crucial.